Pengembangan Media ARASH V Berbasis Android Flashcard untuk Meningkatkan Perbendaharaan Mufradat Siswa MI Nurul Huda Pager - Hasan Syaiful Rizal; Saiful Umar (CV. Satria Jaya, 2024)
The lack of application of learning media causes learning objectives to be not easily achieved, so it is necessary to develop creative and innovative learning media. The purpose of this study was to analyze the effect of Android-based Flashcard learning media. The resulting application is in the form of a file with an .apk extension and is installed on a smartphone with an Android named ARASH V (Arabic Flashcard class V). The development of learning media based on Android uses the RnD (Research and Development) method by adapting the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were students of class V MI. Data collection using pre-test and post-test in one group design. Data analysis used quantitative descriptive analysis method. From the results of observations of student activities while using the media and obtained the results of the average pretest score of 34.17 and the posttest average value of 78.33. Based on the results of data analysis, it can be concluded that the Android-based Flashcard learning media is declared effective for use in learning Arabic vocabulary. The implication of this research is to increase learning motivation, making it easier for students to memorize Arabic vocabulary.